2019
DOI: 10.1016/j.brs.2018.12.450
|View full text |Cite
|
Sign up to set email alerts
|

Optical inactivation of the anterior cingulate cortex modulate descending pain pathway in a rat model of trigeminal neuropathic pain created via chronic constriction injury of the infraorbital nerve

Abstract: Purpose: The anterior cingulate cortex (ACC) plays a critical role in the initiation, development, and maintenance of neuropathic pain. Recently, the effects of optical stimulation on pain have been investigated, but the therapeutic effects of optical stimulation on trigeminal neuralgia (TN) have not been clearly shown. Here, we investigated the effects of optical inhibition of the ACC on TN lesions to determine whether the alleviation of pain affects behavior performance and thalamic neuron signaling. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Studies have revealed that the pain-modulatory action of ACC neurons may be mediated by descending projections. Optogenetic inhibition of the ACC decreases the discharges of sensory thalamic neurons [86,87], while activation or inhibition of the ACC-dorsomedial striatum circuit enhances or attenuates nociception and neuropathic pain [88], both indicating that the thalamus and striatum are involved in the painmodulating circuitry of the ACC. In addition, activation of neurons projecting to the spinal cord potentiates spinal excitatory transmission and causes behavioral hypersensitivity, while inhibiting these projections has an analgesic effect [35], demonstrating that besides the subcortical brain regions, the spinal cord is modulated directly by the ACC.…”
Section: Cerebral Cortexmentioning
confidence: 99%
“…Studies have revealed that the pain-modulatory action of ACC neurons may be mediated by descending projections. Optogenetic inhibition of the ACC decreases the discharges of sensory thalamic neurons [86,87], while activation or inhibition of the ACC-dorsomedial striatum circuit enhances or attenuates nociception and neuropathic pain [88], both indicating that the thalamus and striatum are involved in the painmodulating circuitry of the ACC. In addition, activation of neurons projecting to the spinal cord potentiates spinal excitatory transmission and causes behavioral hypersensitivity, while inhibiting these projections has an analgesic effect [35], demonstrating that besides the subcortical brain regions, the spinal cord is modulated directly by the ACC.…”
Section: Cerebral Cortexmentioning
confidence: 99%